Open reduction, acetabular and femoral head fixation of Pipkin type IV fracture in an adolescent: A Case Report - Bastomi, Ismail; Mulyadi, Dicky (Indonesian Hip and Knee Society (IHKS), 2023)
Femoral head fracture is extremely rare in adolescent. There are few studies that focus on cases treated of pipkin type IV. A 15-year-old male adolescent suffered a serious traffic accident when he was sitting on the front seat of car. Several hours after accident at the local hospital, he diagnosed as posterior dislocation of the right hip with drop foot , and treat closed reduction immobilisation with skin traction. After first operation he transferred to another hospital. Pelvic radiograph computed tomography revealed a head femoral fracture and large acetabular rim fracture. This was diagnosed as a Pipkin type IV acetabular and femoral head fracture with dislocation. An open reduction Inion Freedom bioscrew fixation of head femur and 4.5 cortical screw fixation of acetabular fracture was performed via a Kocher Langenbeck approach. After 1-year follow-up, the patient could walk without aid and participate in physical activities. The X-ray results showed that the fractures healed well with no evidence of complications. Open reduction, fixation both acetabular and femoral head is an available therapy to treat Pipkin type IV in adolescent